TASTAFI SEBAGAI MATERI DAKWAH ULAMA DAYAH DI ACEH - Zulfikar Zulfikar (AL-ILMU, 2021)
This research is to examine the development of the Da'wah of Ulama Dayah in Aceh, where the material for the Da'wah of Tasauf, Tauhid and Fiqh (TASTAFI) is a breakthrough that was proclaimed by Ulama Dayah in Aceh in 2018, so that Tastafi becomes an interesting da'wah material for the adult community. this. In particular, it has provided a change in the use of da'wah media by preachers in Aceh. The Tastafi da'wah material presented by Ulama Dayah is expected to be able to answer various problems that arise in society, both those relating to faith, muamalah, worship and other issues that are polemics in society. The figures who developed the Tastafi da'wah material were Dayah clerics who were already well-known in Aceh Province, so that the Tastafi da'wah material was easily accepted by the public and became a new and interesting da'wah material for the people of Aceh. Tastafi da'wah materials carried out by Ulama Dayah have so far been carried out openly and some have been broadcast live streaming through several social media, so that this makes it easier for people who want to follow Tastafi da'wah materials anywhere da'wah activities are carried out. Tastafi da'wah activities are also carried out thoroughly in Aceh Province, so that all people who want to follow Tastafi da'wah materials can directly or live streaming social media.